Computer modeling of oxygen containing heptylamines as monoamine oxidase inactivators - (:unkn) unknown (ELSEVIER SCIENCE BV, 2001)
Monoamine oxidase is a flavoenzyme that catalyzes the oxidation of amines. Primary amines are excellent substrates for MAO but primary amine analogues having an electron withdrawing group near the amino methyl methylene group are known to inactivate the enzyme. In order to investigate the proposed inductive effect, a series of amino ethers and their enzyme-adduct models were studied with Self Consistent Field theory using a semi-empirical PM3 method and an ab initio method at the MP2/6-31G*//6-31G* level. According to the proposed inactivation mechanism, the stabilities of the adducts are inversely related to the enzyme reactivation rate. Therefore, we interpreted the order of enzyme reactivation rate in terms of intramolecular stabilization and stereoelectronic effects. Calculations predicted that intramolecular H-bonding interactions and CH(2)/O nonbonded interactions play important roles in the stability of these molecules. In enzyme-adducts, we also found out a special SCH(3)/N type of nonbonded interaction and negative hyperconjugation in the -SCH(2)NH(2) fragment. (C) 2001 Elsevier Science BN. All rights reserved.
Keywords: monoamine oxidase B; hydrogen bonding; nonbonded interactions; ab initio; enzyme adduct; AGENT MILACEMIDE 2-(N-PENTYLAMINO)ACETAMIDE; MO AB-INITIO; CONFORMATIONAL BEHAVIOR; GAS-PHASE; 1,2-DIMETHOXYETHANE; HYPERCONJUGATION; STABILIZATION; SPECTROSCOPY; MOLECULES; MECHANISM